MANAJEMEN PENGEMBANGAN PENDIDIKAN KECAKAPAN HIDUP BAGI ANAK BERKEBUTUHAN KHUSUS DENGAN RETARDASI MENTAL DI SLB - Mursiawati, Mursiawati; Sukmawati, Sukmawati; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study is 1) Educational development planning Life skills 2) Steps in  lifeskills   education   service  3) Evaluation  of  life  skills  education  services  4)  Supporting,  matters   in  the  implementation  of  life  skills  education  services 5) Efforts  to  overcome  obstacles  in  implementing  life  skills  education  services. This research uses a qualitativeapproach, carried out in SLB-C Dharma Asih Pontianak  with  the subject of the Principal, the informants are curriculum waka, teachers and students. The study was conducted  from January  to  March   2019.  Data   sources  used   were   documentation,   observation   and interviews.  The  data  validity  technique  uses  triangulation  techniques,  namely:  source triangulation,  method  triangulation,  investigator  triangulation, and theory triangulation. The  collection  technique  uses  primary  and  secondary data. The results of the study are:1) Management  of  developing  life skills  education  for life skills for children with special needs  with  mental  retardation  in  Dharama Asih Pontianak SLB-C. namely managementConducted  in  SLB  has  been  carried  out,  from planning, implementation, supervision to evaluation  Skill  teachers  have the responsibility of each, towards their students, but thereare some things that are lacking in delivery so that education is confused about the existing planning,  because  it  directly  submits  to  the respective  skill  units.  Its  development and preparation  are  carried  out  in  accordance  with  teaching  and learning activities left to educators  and  teacher  skills.  In  the  implementation is less than the maximum due to the factor of children not going to school, as well as supervision and evaluation of the skills  of each  teacher  each  unit  is  less  effective  2) Obstacles  in  the implementation of life skills education  services  for children with special needs with mental retardation in SLB namely: lack  of  coordination with teachers in the field of study about the expected plan, the factors of  students  who are easily tired, tired, easily offended so they do not want to participate in teaching  and  learning  activities  3) solutions  to  learning  methods  vary in providing life skills  education  services  for  children  with  special  needs  with basic skills in the field of entrepreneurship, for example: making eggs salted from the manufacturing  process  to  themarketing  of  students  trained  and fostered, by classroom teachers and skill teachers who have junior-high and LB-high  education,  the  level  of disability is mild retardation that is able  to    educate   and   be  able   to   train.   Students  are  fostered,  trained  with  smooth communication  and  given rewards to students, so that the learning process is comfortable and enjoyable. Keywords: Management, Life Skills, Children With Special Needs